Sistem Informasi Rekam Medis Pada RSU Elpi Al-Aziz Menggunakan Bahasa Pemrograman VB.NET 2010 - Syah Ramdani Siregar (Jurnal Informatika, 2022)
RSU Elpi Al-Aziz is an agency engaged in public health services. At RSU Elpi Al-Aziz, in providing services to patients, drug data collection, prescriptions and reports are still done manually or not computerized. Patient data storage media using paper media resulting in the search for data is done by browsing the archives that can take time and prescription making is still done by handwriting where there can be errors recording and making reports related to medical records are still done manually by recording patient data through archives that can take time but it is vulnerable to errors. To support the development method of Medical Record Information System that is made now the author uses the waterfall method by using system development tools in the form of flowcharts, context diagrams, DFD, and database design tools proposed in the form of ERD. As well as data collection techniques with research methods by observation, interviews and literature studies. Implementation of the computer program used in this medical record information system using Visual Basic 2010 programming language with MySQL database that provides facilities to facilitate the process of making information systems and product implementation. The Information System created can overcome the problems that exist in RSU Elpi-Aziz. Storage Media, processing of patient data, medical records, and drugs have been computerized so that the process of public health services can be done quickly and avoid mistakes and facilitate performance at RSU Elpi Al-Aziz.